The activity-based methodology to assess ship emissions - A review - R. A. O. Nunes (2017)
Several studies tried to estimate atmospheric emissions with origin in the maritime sector, concluding that it contributed to the global anthropogenic emissions through the emission of pollutants that have a strong impact on hu' health and also on climate change. Thus, this paper aimed to review published studies since 2010 that used activity-based methodology to estimate ship emissions, to provide a summary of the available input data. After exclusions, 26 articles were analysed and the main information were scanned and registered, namely technical information about ships, ships activity and movement information, engines, fuels, load and emission factors. The larger part of studies calculating in-port ship emissions concluded that the majority was emitted during hotelling and most of the authors allocating emissions by ship type concluded that containerships were the main pollutant emitters. To obtain technical information about ships the combined use of data from Lloyd's Register of Shipping database with other sources such as port authority's databases, engine manufactures and ship-owners seemed the best approach. The use of AIS data has been growing in recent years and seems to be the best method to report activities and movements of ships. To predict ship powers the Hollenbach (1998) method which estimates propelling power as a function of instantaneous speed based on total resistance and use of load balancing schemes for multi-engine installations seemed to be the best practices for more accurate ship emission estimations. For emission factors improvement, new on-board measurement campaigns or studies should be undertaken. Regardless of the effort that has been performed in the last years to obtain more accurate shipping emission inventories, more precise input data (technical information about ships, engines, load and emission factors) should be obtained to improve the methodology to develop global and universally accepted emission inventories for an effective environmental policy plan.